HUBUNGAN KARIES GIGI DENGAN UMUR DAN JENIS KELAMIN SISWA SEKOLAH DASAR DI WILAYAH KERJA PUSKESMAS KALIWATES DAN PUSKESMAS WULUHAN KABUPATEN JEMBER - Kiswaluyo, Kiswaluyo (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Dental health problem in Indonesia is interesting to be studied since it reaches 80% of population. This study was conducted on the elementary school students in the working area of Kaliwates and Wuluhan Public Health Centers in Jember Regency in 2008 aiming at knowing the relations between dental caries and age as well asgender. The result showed that gender was not related to studentsâ dental caries, while age showed relation to the studentsâ dental caries.